Pinning control of complex networked systems : synchronization, consensus and flocking of networked systems via pinning - Su, Housheng, author; Wang, Xiaofan, author (Berlin : Springer ; Shanghai : Shanghai Jiao Tong Univ. Press)
Synchronization, consensus and flocking are ubiquitous requirements in networked systems. Pinning Control of Complex Networked Systems investigates these requirements by using the pinning control strategy, which aims to control the whole dynamical network with huge numbers of nodes by imposing controllers for only a fraction of the nodes. As the direct control of every node in a dynamical network with huge numbers of nodes might be impossible or unnecessary, it's then very important to use the pinning control strategy for the synchronization of complex dynamical networks